2017
DOI: 10.1002/ejic.201700554
|View full text |Cite
|
Sign up to set email alerts
|

Revealing the Nature of Bonding in Rare‐Earth Transition‐Metal Tellurides by Means of Methods Based on First Principles

Abstract: Tellurium-rich rare-earth (R) transition-metal tellurides with low-dimensional Te networks provide alluring systems to explore the formations of charge density waves (CDWs). The lack of knowledge concerning the bonding in Te-rich rare-earth transition-metal tellurides inspired us to determine the electronic structures and the nature of bonding for two prototypical examples, namely LaCu 0.28 Te 2 and Gd 3 Cu 2 Te 7 , by means of methods based on first principles. From chemical bonding anal- [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…Under consideration of previous research [37,38] on the electronic structures of alkaline-metal-containing polar intermetallics, this outcome suggests that the Rb-Te interactions should be considered as ionic interactions, while the Pr-Te and Ag-Te interactions should be regarded as rather strong, polar, mixed-metal bonds. This outcome also indicates that a full valence-electron transfer as proposed by an application of the Zintl-Klemm concept should be regarded with suspicion-a consequence which has also been identified by recent explorations of the electronic structures of rare-earth transition-metal tellurides [22] as well as silver tellurides [21]. The homoatomic Ag-Ag interactions change from bonding to considerable antibonding states at −4.41 eV, which may be regarded as attributes of the d 10 -d 10 closed-shell [39,40] interactions; however, the Ag-Ag -ICOHP values are indicative of a net bonding character for these interactions.…”
Section: Electronic Structure and Chemical Bonding Analysismentioning
confidence: 76%
See 2 more Smart Citations
“…Under consideration of previous research [37,38] on the electronic structures of alkaline-metal-containing polar intermetallics, this outcome suggests that the Rb-Te interactions should be considered as ionic interactions, while the Pr-Te and Ag-Te interactions should be regarded as rather strong, polar, mixed-metal bonds. This outcome also indicates that a full valence-electron transfer as proposed by an application of the Zintl-Klemm concept should be regarded with suspicion-a consequence which has also been identified by recent explorations of the electronic structures of rare-earth transition-metal tellurides [22] as well as silver tellurides [21]. The homoatomic Ag-Ag interactions change from bonding to considerable antibonding states at −4.41 eV, which may be regarded as attributes of the d 10 -d 10 closed-shell [39,40] interactions; however, the Ag-Ag -ICOHP values are indicative of a net bonding character for these interactions.…”
Section: Electronic Structure and Chemical Bonding Analysismentioning
confidence: 76%
“…To provide an insight into the bonding situation in RbPr2Ag3Te5, we followed up with an examination of the crystal orbital Hamilton population curves (COHP; Figure 2) and their respective integrated values (Table 3). In this context, the cumulative -ICOHP/cell values, i.e., the sums of the negative ICOHP/bond values of all nearest neighboring contacts within one unit cell, were projected as percentages of the net bonding capabilities for each sort of interaction to identify roles of the diverse interactions in overall bonding-a procedure that has been largely employed elsewhere [21,22,[33][34][35][36]. (Figure 2) reveals that the occupied states close to the Fermi level, E F , originate to a large extent from the Ag-d and Te-p atomic orbitals beside minor contributions from the Pr-d states.…”
Section: Electronic Structure and Chemical Bonding Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the light of such relevance for research and technical applications, one could also expect that the nature of bonding in tellurides is typically examined employing first-principles-based approaches; yet, the electronic structures, particularly the nature of bonding, in many tellurides are frequently (and simplistically) interpreted by applying the Zintl-Klemm concept rather than first-principles-based bonding analyses [15]. More recent research [16][17][18] on the electronic structures of certain tellurides, however, demonstrated that such Zintl-Klemm pictures should be taken with a pinch of salt. In fact, examining the electronic structures of (active-metal) transition-metal tellurides (active-metal = group I and III elements) revealed that the bonding nature in these tellurides is dominated by strong transition-metal−tellurium interactions beside minor transition-metal−transition-metal or tellurium−tellurium interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Additional inspections of the X-ray diffraction patterns of SmCu0.34Te2 being isostructural with LaCuxTe2 (0.28 ≤ x ≤ 0.50) bared the presence of weak reflections pointing to a superstructure along the direction of the linear tellurium chains. Recent quantum chemical examinations [124] on the nature of bonding in these rare-earth copper tellurides showed the paramount role of heteroatomic R-Te bonding for these materials; however, the degrees of distortions within the linear tellurium chains appear to be influenced by the amounts of copper in the tellurides: a gedankenexperiment demonstrates that the Te chains can distort, a gap opens at the Fermi level and the overall bonding is maximized as the copper content is reduced. Another example of a telluride whose electronic structure cannot be categorized by applying the Zintl-Klemm concept is the mineral stützite, Ag5−xTe3, that crystallizes in a broad homogeneity range (1.44 ≤ x ≤ −0.25) [125].…”
Section: Tendencies Within Bonding Motifs In Compounds With Polyanionmentioning
confidence: 99%